Intrauterine Condom Tamponade in Management of Post Partum Hemorrhage - Joshi, Rijuta; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To analyze the outcome of intrauterine balloon tamponade using fluid filled latex condom attached to Foley’s catheter (condom tamponade) in the management of postpartum hemorrhage. Methods: This is a retrospective descriptive study of 29 women with postpartum hemorrhage unresponsive to pharmacological agents and managed with condom tamponade in Paropakar Maternity and Women’s Hospital, Nepal from 13th February 2015 to 12th February 2016. Data were entered in Microsoft office excel (2007). Results: Majority (n=20) of women were 20-29 years and 52% of them (n=15) were primipara. Seventy percent women (n=20) delivered at term and vaginal delivery was the most common mode of delivery (72.41%, n=21). Sixty-two percent (n=18) had blood loss of <1000ml and condom tamponade was successful in 27 out of 29 women. One woman each needed internal iliac artery ligation and peri-partum hysterectomy. Conclusions: Intrauterine condom tamponade is the effective method of arresting postpartum hemorrhage due to a wide variety of causes.